PENGARUH BRAND EXPERIENCE TERHADAP BRAND LOYALTY MELALUI PERCEIVED QUALITY DAN BRAND TRUST PADA PENGGUNA SMARTPHONE DI JAKARTA - Anindita, Rangga Anung; Pakpahan, Arnolt Kristian (Business, Economics dan Entrepreneurship, 2024)
The objective of the empirical study is to examine and to analyze the effect of Brand Experience on Brand Loyalty mediated by Perceived Quality and Brand Trust of smaprtphone users in Jakarta, with 188 respondents as samples. In this study, the sampling method used non-probability sampling, using purposive sampling technique. The data analysis methods used are Structural Equation Modeling (SEM), SPSS and AMOS24 software. The results show (1) Brand Experience variables have no positive effect on Brand Loyalty and is not supported. (2) Brand Experience variables have a positive effect on Perceived Quality and is supported. (3) the Brand Experience variables have a positive effect on Brand Trust and is supported. (4) Perceived Quality variables have a positive effect on Brand Loyalty and is supported. (5) Brand Trust variable has a positive effect on Brand Loyalty is supported. (6) Brand Experience variable has a positive effect on Brand Loyalty which is mediated by Perceived Quality and is supported. (7) Brand Experience variable have no positive effect on Brand Loyalty which is mediated by Brand Trust and is not supported.